Estimation Of Soil Erodibility On Different Land Covers In Urung Kompas Village, South Rantau District, Labuhanbatu Regency - Yuli Ferdiansyah, Wan; Syawal Harahap, Fitra; Walida, Hilwa; Ayu Putri Septiyani, Ika (CV. Inara, 2023)
There will be widespread damage to the land as a result of land degradation, particularly to forest land. Changes in land use from extremely durable vegetation to escalated agrarian land make the dirt all the more handily disintegrated. One of the deciding variables of disintegration is soil disintegration and soil cover vegetation. Soil erodiability is the typical measure of soil lost every year per unit of the file, while the land cover is helpful for safeguarding the dirt from the danger of harm by disintegration and further developing soil conditions. The exploration was done from October 2022 to June 2023. In January 2013, field sampling was carried out. The technique utilized in this study was the review strategy and the purposive examining technique. Choose three points of observation. Then, in the laboratory, data analysis and field observation. Assessment of soil erodibility is completed by taking soil tests, deciding soil structure, soil porousness in the field, and deciding soil surface and natural matter for examination in the research center. Distinguishing proof of disintegration by taking documentation of kinds of disintegration that alludes to references and realities tracked down in the field. To decide the worth of erodibility (soil aversion to disintegration) utilizing a nomograph (soil erosibility). Results of the Study Soil erodibility on oil palm land in the Urung Kompas Village was low to medium, ranging from 0.17 to 0.26. The research site on oil palm land in the Urung Kompas subdistrict has five types of erosion: trench erosion, splash erosion, sheet erosion, furrow erosion, and landslides.